USE OF FILM SCRIPTS AND THEIR TRANSLATIONS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Buğra Zengin (Informascope, 2019)
Although millions of EFL learners benefit from watching subtitled/captioned movies and TV shows in non-instructional settings, one almost untouched area is the development of strategies in benefiting from film scipts and their translated versions as well as audio language-subtitle combinations. This paper reports research subseqent to the researcher/teacher's guided work on the use of film scripts and their translated versions to notice and list chunks as well as technical and creative use of language in these scripts with their immediate contexts comparing the original scripts and those translated in Turkish and do creative dialogue/anecdote writing focusing on appropriacy and variety in language use despite some students' self-reported lack of focus on the jargons and formal language. The research was conducted with 1-5 Likert type questionnaires and closed-ended yes/no questions. The participants, the students of the research/teacher of the present paper, are the undergraduate students taking advanced language skills course as part of the curriculum of their major, the English language and literature. The results demonstrated that the film scripts can be used to convert the input provided by the film scripts to intake and uptake, and provide good examples regarding the application of own language use in ELT.